(untitled) (Biological Sciences - PJSIR, 2018)
Present investigation was carried out to estimate the correlation and regression coefficient estimates between some growth performance traits of Harnai sheep. The available data was collected and maintained at Multipurpose Sheep Research Centre Yetabad, District Loralia, Balochistan, Pakistan. The data regarding growth traits including birth weight, yearling weight, weaning weight and fleeces weight was analysed for the estimation of correlation and regression coefficient. In present study the results for correlation and regression coefficient estimates were observed low to positive between some growth performance traits of Harnai sheep. Due to low results for correlation and regression coefficient, it is concluded that mass selection is advisable for achieving better performance in growth traits of Harnai sheep.